Determination method of high fluence rate for D-T neutron source with long counter. (November 2021) - Li, Yanan; Li, Taosheng; Wang, Ying; Hong, Bing; Wang, Feipeng
Abstract: A method of determining high fluence rate for D-T neutron source by using two long counters is introduced. One long counter contains a BF3 proportional counter, and a response of 1.1 cm 2 is determined by calibration. The other long counter contains a gamma compensated boron neutron ionization chamber, and a response of 2.06e-5 cm 2 is determined by comparing with the results of long counter containing BF3 proportional counter. By appropriately arranging the two long counters, fluence measurements are performed at the high intensity D-T neutron generator (HINEG). The results of the experimental characterization to the long counter are presented at this paper. Highlights: A method to determine high fluence rate with two long counters is described. A gamma compensated boron neutron ionization chamber is used for high fluence. Fluence measurements are performed in high-intensity D-T neutron field.